Analisis Kelayakan Usaha Gula Aren di Desa Bonto Katute Kecamatan Sinjai Borong: Feasibility Analysis of Palm Sugar Business in Bonto Katute Village, Sinjai Borong District - Darmawan, A. Muh Alfian; Megawati, Megawati; Astaman, Putra; Nurdin, Fadilah (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study aims to analyze the income and financial feasibility of the palm sugar business in Bonto Katute Village, Sinjai Borong District. The research method used was a survey with a quantitative approach. The sample was selected using purposive sampling, consisting of 47 palm sugar farmers who already possess a Halal Certificate. Data were collected through observation, interviews, and questionnaires, while the financial feasibility was analyzed using the Revenue Cost Ratio (R/C) indicator. The results of the study show that the average net income received by palm sugar farmers is IDR 2,506,154 per month. Based on the feasibility analysis, this business obtained an R/C Ratio value of 2.37. This value indicates that for every IDR 1 of cost incurred, it generates a revenue of IDR 2.37. Therefore, it can be concluded that the palm sugar business in Bonto Katute Village is highly feasible to be pursued and developed.